2023
DOI: 10.1038/s41467-023-36148-1
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived extracellular vesicles increase insulin secretion through transport of insulinotropic protein cargo

Abstract: Adipocyte-derived extracellular vesicles (AdEVs) are membranous nanoparticles that convey communication from adipose tissue to other organs. Here, to delineate their role as messengers with glucoregulatory nature, we paired fluorescence AdEV-tracing and SILAC-labeling with (phospho)proteomics, and revealed that AdEVs transfer functional insulinotropic protein cargo into pancreatic β-cells. Upon transfer, AdEV proteins were subjects for phosphorylation, augmented insulinotropic GPCR/cAMP/PKA signaling by increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…EVs can directly or indirectly influence insulin resistance by promoting these proinflammatory responses, or dysregulating insulin signaling and down-regulating glucose transporter expression . Conversely, treatment with MSC-derived EVs can increase glucose tolerance in the T2DM animal model, and recent evidence suggests that adipocyte-derived EVs secreted during excess weight gain can promote glucose secreted insulin secretion to attenuate the development of insulin resistance . Thus, EV therapeutics may have the potential to attenuate or reverse the underlying mechanisms responsible for T1DM and T1DM.…”
Section: Ev Diagnostic Prognostic and Therapeutic Applicationsmentioning
confidence: 99%
“…EVs can directly or indirectly influence insulin resistance by promoting these proinflammatory responses, or dysregulating insulin signaling and down-regulating glucose transporter expression . Conversely, treatment with MSC-derived EVs can increase glucose tolerance in the T2DM animal model, and recent evidence suggests that adipocyte-derived EVs secreted during excess weight gain can promote glucose secreted insulin secretion to attenuate the development of insulin resistance . Thus, EV therapeutics may have the potential to attenuate or reverse the underlying mechanisms responsible for T1DM and T1DM.…”
Section: Ev Diagnostic Prognostic and Therapeutic Applicationsmentioning
confidence: 99%
“…[17][18][19][20][21] In this context, several studies have shown that the proteins contained in AdEVs, as well as miRNAs, can be transferred to target cells to modulate their activity. [22][23][24] For example, EVs released by adipocytes of mice under high fat diet (HFD) modulate insulin metabolism in target cells through their proteinaceous cargo. [24] In addition, AdEVs also modulate macrophage polarization using miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] For example, EVs released by adipocytes of mice under high fat diet (HFD) modulate insulin metabolism in target cells through their proteinaceous cargo. [24] In addition, AdEVs also modulate macrophage polarization using miRNAs. [25,26] Recent studies support the idea that AdEVs lipids may also play a role in energy homeostasis and the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actively shed by cells, EVs carry molecular components (proteins, nucleic acids, and other metabolites) of parental cells . Present in most body fluids, EVs participate in cell–cell communications, , immune response, and cancer metastasis. , Tumor-derived EVs (tEVs) can serve as a class of biomarkers for cancer diagnosis. Profiling the type and expression level of surface proteins of cancer-related EVs enables identifying cancer origins and classifying cancer types. Accurate detection of tEVs is still challenging.…”
mentioning
confidence: 99%